Least squares parameter estimation in chaotic differential equations - Kallrath, Josef; Schlöder, Johannes P.; Bock, Hans Georg (Celestial mechanics and dynamical astronomy, 1993)
A recent least squares algorithm, which is designed to adapt implicit models to given sets of data, especially models given by differential equations or dynamical systems, is reviewed and used to fit the Hénon-Heiles differential equations to chaotic data sets.
Gesehen am 14.06.2023